PENGARUH KEPEMIMPINAN DALAM PERUBAHAN ORGANISASI - Utami, Setyaningsih Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABTRACT To comprehend change management represent principle in growth an organization. This change is triggered from environment that changing dynamically, either from external environment and also internal environment of organization. Organizational change is not matter which is easy to be done. There are many constraints which can block change program, for example: organization system constraints and power, difference in functional orientation and organization chart which is mechanistic, organizational culture, group norm, groupthink and individual constraints, like is not ready to resulting to feel uncertainty, worry, and no peaceful. Organizational change oftentimes cannot be let happened "naturally" just. Change oftentimes requires to be designed, to be engineered and managed by a strong leadership, visionary, smart, and orient development. In the middle of intensively environmental change, without effort change of correct organizational under strong leadership, visionary, smart, and orient development, an organization will limp, even possibly will die to be castigated by its strength of change current. Keywords: change management, organizational system, functional orientation, organizational culture, norm, groupthink, visionary, smart, orient development